A Cassava Washing Appliance Design for The Home Industry - Safitri, Riska; Zadry, Hilma; Saputra, Dendi Adi; Amin, Muhammad (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
The food business opportunity is very interesting for home industry entrepreneurs in West Sumatra, a home industry of cassava chips. The step of the cassava chip production process that takes longer time than the other step is the washing process. The cassava washing process is carried out manually because washing device that uses motor drives are not affordable for home industry entrepreneurs. In addition, the cassava washing process makes a physical complaint from the operators. Therefore, this research designs a cassava washer that is affordable for the home industry by considering design methods, ergonomic aspects, and customers' needs. This design is carried out using the Quality Function Deployment (QFD) method to translate the voice of the customer into technical and design characteristics, morphological charts for generating alternative designs, and an objective weighted method for evaluating that alternative. The result of this research is the design of a cassava washer which is more practical because it makes the operator works easier and can save time in the washing process. It is also very affordable, with an estimated cost of production IDR2,397,743.